STUDY OF MARMAS IN LOWER EXTREMITY WITH SPECIAL REFERENCE TO URVI MARMA - J. Pathan, Rubina; Nikumbh, Milind B.; Rathod, Sanjay T.; Dawre, Manisha (International Journal of Ayurveda and Pharma Research, 2017)
Marma (vital point) science is one element of Ayurveda gifted by Acharyas. It is not much developed in modern science. Marma are vital point on body surface having importance regarding traumatic effect. Marma is vital point where injury occur can lead to disability, dysfunctioning or even termination of life. Every aspect of Marma like definition, signs symptoms of Marma injury was thoroughly explained by Acharya Sushrut. Not only the Marma but also the Marma Viddha Lakashana (after effect injury) was documented by Acharya Sushrut. These Lakshanas (symptoms) shows similarity with the sign & symptoms occur due to the trauma at that site. It is an need of an hour to find out the exact structure present at Marma site so as to prevent disability or deformity effect after injury. Here we are studying Urvi Marma, which lies in the middle of the thigh as given in Samhita Granthas. As per modern anatomy in the middle region of thigh, there is structure of adductor canal. Adductor canal contains femoral artery, femoral vein, which are major blood vessels of lower limb. Urvi Marma which has been described as Sira Marma (vascular vital point) & Vaikalyakara Marma (deformity) by Acharyas. The present study is done to trace the exact location of Urvi Marma according to modern anatomy, so that actual structure present at that site can be known which helps to elaborate Vidha lakashana (injury effect) of Urvi Marma.